(untitled) (Global Journal of Science Frontier Research, 2023)
The article proposes Lev Sapogin s unitary model of the atom and atomic nucleus without quarks and flavors Based on the table of Dmitry Mendeleev where the first cell was occupied by the ether physical vacuum which in the monstrous gravitational electric and magnetic fields of black holes is polarized generating particles and antiparticles I presented the possible assembly of atoms of chemical elements from elementary particles using a very fast plasma centrifuge a quasar